Uma arquitetura de controle para um robô quadrúpede com comportamento reflexivo de estabilidade - Lima, Luis Eduardo Martins de (2007)
This thesis presents a control architecture for a quadruped Robot with 16 degrees of freedom (4 per leg), the Guará* The proposal to develop this architecture aims to set a problem study platform inherent to mobile four-legged robots, such as the walking generation, the complex movement control, the obstacle transposition, and the stability reflex implementation. The challenge faced herein is to endow the robot with sufficient autonomy in order to process on board, the locomotion control and the obstacle transposition strategies, through the use of an architecture which can let an effective interaction of the robot with the environment in which he is navigating, with reduced computational cost. The proposed architecture is based on the hierarchical control paradigm using reflexive behavior. The hierarchical structure of this architecture concentrates the cinematic modeling processing of the robot and the decision making to define the movements to be fulfilled (in a free locomotion or with the presence of obstacles), in the higher control level that is supervisor level, whereas a net communication CAN (Controller Area Network) is used to distribute the information to be processed in the lower level of control (coordinator and actuator level). To allow the reactive interaction of the robot with the navigation environment, focusing the balance stability, Guará’s control architecture uses a two-axis accelerometer which provides information for fuzzy controllers processed in the coordinator level. This configuration defines reactions against undesirable bending of Guará’s platform (dive and rolling) generated in the course of the locomotion.The usage of the hierarchic control contributes to the robustness of the control architecture, establishing the higher control level (supervisor level), and the flexibility to take over distinct and complex tasks (cinematic and dynamic modeling, environment mapping, among others), while lower levels of the control hierarch concentrate on the tasks which demand immediate responses to external stimulus or balance stabilization of the robot.